2016
DOI: 10.1016/j.jaac.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Salience Network Connectivity in Autism Is Related to Brain and Behavioral Markers of Sensory Overresponsivity

Abstract: Objective The salience network, an intrinsic brain network thought to modulate attention to internal versus external stimuli, has been consistently found to be atypical in autism spectrum disorders (ASD). However, little is known about how this altered resting-state connectivity relates to brain activity during information processing, which has important implications for understanding sensory over-responsivity (SOR), a common and impairing condition in ASD related to difficulty downregulating brain responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 40 publications
6
91
1
Order By: Relevance
“…Atypical connectivity and deviating activation of the AI were observed during social and non‐social oddball tasks (Odriozola et al ., ). In children and adolescents with ASD, resting‐state connectivity between the salience network and other attentional networks was positively correlated with sensory over‐responsivity (Green et al ., ). Children with ASD exhibited reduced activation of the ACC, TPJ, inferior frontal gyrus and anterior middle frontal gyrus during a change detection task (Gomot et al ., ).…”
Section: Alerting and Orienting In Children With Asdmentioning
confidence: 97%
“…Atypical connectivity and deviating activation of the AI were observed during social and non‐social oddball tasks (Odriozola et al ., ). In children and adolescents with ASD, resting‐state connectivity between the salience network and other attentional networks was positively correlated with sensory over‐responsivity (Green et al ., ). Children with ASD exhibited reduced activation of the ACC, TPJ, inferior frontal gyrus and anterior middle frontal gyrus during a change detection task (Gomot et al ., ).…”
Section: Alerting and Orienting In Children With Asdmentioning
confidence: 97%
“…The anterior salience network has also been identified in prior case-control studies. In younger cohorts, anterior salience areas are hyperconnected 50,51 , while in older cohorts, hypoconnectivity is observed 52 . While age could be a factor in explaining the discrepant findings from prior work, it likely cannot explain the SC=RRB hyperconnectivity finding.…”
Section: Discussionmentioning
confidence: 94%
“…Volumetric studies have revealed enlarged amygdalae earlier in childhood in ASD relative to typically-developing children [Schumann, 2004]. fMRI studies have revealed decreased or increased activation during social-emotional tasks and aberrant functional connectivity of the amygdala in individuals with ASD compared to typically-developing controls [Baron-Cohen et al, 2000;Green, Hernandez, Bookheimer, & Dapretti, 2016;Guo et al, 2016;Kliemann, Dziobek, Hatri, Baudewig, & Heekeren, 2012]. Although the source of abnormalities in amygdala processing in ASD is not currently well understood, these studies clearly implicate alteration of amygdala circuitry, structure, and function in ASD.…”
Section: Introductionmentioning
confidence: 99%